The Impact of Creativity, Innovation and Motivation of Bio-Entrepreneurship Students on Recycled Products - Wilda Widiawati; Burnama Azhari; Rista Astari Rusdin; Nur Ulfah; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2023)
Creativity and innovation can improve the quality of life because personal time must be used to do something useful. It is common to everyone, anytime and anywhere, regardless of age and education. The purpose of this study was to determine the relationship between the creativity and innovation of bioentrepreneurial students and recycled products. The main population of this study were 15 students of the Bioentrepreneurship study program. The results of the study reveal that the relationship between creativity and innovation variables is an indicator of the process in which material (Y1,...Y4) is transformed into a process activity (Y5,...Y8) and reduces the amount of waste. Y9,...Y12). Based on the data in the table above, the recycling indicator is reprocessing used materials into new materials so that nothing can really be obtained from the waste with an average of 3.78, where the recycling indicator is the processing of used nuclear fuel . . . for the value of benefits with an average of 3.49 and for reducing the amount of waste to reduce pollution is 3.50, so the ratio of creativity and innovation of bio-entrepreneurship students to recycled products is an average of 3.59, which means that the ratio of creativity and innovation of bio-entrepreneurship students towards recycled products is good or significant.